Contribuição ao desenvolvimento de um laboratório de arcos elétricos para a medição da energia incidente - Bacin, Pedro de Oliveira (2022)
The arc flash is an event of stochastic behavior caused by the rupture of the dielectric strength between two or more conductors, from conditions that favor its appearance. Its high destructive potential and the resulting incident energy generates a high electrical risks to equipments and workers. Given the severity of this event, since 1980, there has been an increase in research and laboratory tests in the subject, which focused on a better understanding of the phenomenon and which allowed the creation of mathematical models for the estimation of incident energy, which enabled the arising of more effective safety measure against these events. Also, standards related to the subject were created, such as IEEE Std 1584-2018 and NFPA 70E, at the international ambit, and national standards, such as NR-6, NR-10 and ABNT NBR 16384:2020, with a more supperficial approach. Despite this, due to the great technical complexity and associated implementation costs, there are still few high-current laboratories in the world that carry out technical research related to electric arcs. Considering the different situations that can culminate in an arc f lash, there are still points that need to be clarified and that are not directly addressed in the current regulations, such as weather conditions (for example: humidity), besides more diversified configurations and gaps between electrodes. Thus, a laboratory with a structure to generate high short-circuit currents for arc flash tests was built at the Institute of Intelligent Networks (INRI) of UFSM, in a partnership with CPFL Energy group. The structure of the laboratory makes possible to establish the arc flash and control its extinction for times up to two seconds, and among its equipments, stands out a threephase transformer of 5 MVA and three single-phase reactors capable of controlling the levels of short-circuit currents, furthermore an incident energy measurement system that involves calorimeters with copper discs and a high-speed thermographic camera to record the temperature increase in the calorimeters. The results found certify that the laboratory succed to perform safely arc flash tests through the adopted laboratory’s procedures, and that the implemented measurement system can reliably estimate the incident energy, in order that on the horizon it will be possible to explore issues that are not addressed in the main current normative references.